2022
DOI: 10.3389/fneur.2022.851910
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Tirofiban During Intravenous Thrombolysis Bridging to Mechanical Thrombectomy for Acute Ischemic Stroke Patients: A Meta-Analysis

Abstract: IntroductionThe safety and efficacy of tirofiban in intravenous thrombolysis (IVT) bridging to mechanical thrombectomy in patients with acute ischemic stroke (AIS) is unknown. The purpose of this meta-analysis was to evaluate the safety and efficacy of tirofiban in IVT bridging to mechanical thrombectomy in acute ischemic stroke.MethodsWe systematically searched PubMed, EMBASE, Web of Science, and The Cochrane Library, CNKI, and Wan Fang databases for randomized controlled trials and observational studies (cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Several studies reported that tirofiban could lead to neurological deterioration by increasing ICH risk, 19 and a meta‐analysis of 7 studies revealed that tirofiban was not associated with higher rate of ICH but trended toward lower mortality. 20 However, most of these studies did not report detailed information about the dose or the duration of intraarterial tirofiban in their cohorts. 16 , 19 , 20 A recent study from Guo et al illustrated that half of the patients receiving intravenous tirofiban were also treated with intraarterial local tirofiban in clinical practice in China, and simultaneous intraarterial+intravenous tirofiban rather than intravenous tirofiban improved outcomes of patients with anterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that tirofiban could lead to neurological deterioration by increasing ICH risk, 19 and a meta‐analysis of 7 studies revealed that tirofiban was not associated with higher rate of ICH but trended toward lower mortality. 20 However, most of these studies did not report detailed information about the dose or the duration of intraarterial tirofiban in their cohorts. 16 , 19 , 20 A recent study from Guo et al illustrated that half of the patients receiving intravenous tirofiban were also treated with intraarterial local tirofiban in clinical practice in China, and simultaneous intraarterial+intravenous tirofiban rather than intravenous tirofiban improved outcomes of patients with anterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, most of these studies did not report detailed information about the dose or the duration of intraarterial tirofiban in their cohorts. 16 , 19 , 20 A recent study from Guo et al illustrated that half of the patients receiving intravenous tirofiban were also treated with intraarterial local tirofiban in clinical practice in China, and simultaneous intraarterial+intravenous tirofiban rather than intravenous tirofiban improved outcomes of patients with anterior circulation stroke. 16 In our preceding RESCUE‐BT trial, we found that intravenous tirofiban preceding thrombectomy failed to improve the clinical outcomes of patients with anterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Currently, effective treatments for ischemic stroke include early restoration of cerebral perfusion and salvage of the ischemic semidark zone. [4] Tissue-type fibrinogen activator (rt-PA, alteplase) is the only approved therapeutic agent for revascularization and improvement of neurological deficits. However, it is limited by the time window and the risks of hemorrhagic transformation and neurotoxicity, making it possible to benefit from it in only 2% to 5% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Currently, effective treatments for ischemic stroke include early restoration of cerebral perfusion and salvage of the ischemic semidark zone. [4]…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there may be a failure of recanalisation or early re-occlusion. A meta-analysis of seven randomised controlled trials and observational studies involving 1175 patients given tirofiban, a GPIIb/IIIa receptor antagonist, or control, showed reduced peri-operative re-occlusion, but did not show better recanalisation or 3-month functional outcome, nor increased symptomatic intracranial haemorrhage (ICH) [ 14 ]. Cai et al performed a retrospective study of 285 patients who underwent thrombectomy for anterior circulation large artery occlusion, mean age 71 years, 61.7% female [ 15 ].…”
mentioning
confidence: 99%